Calnexin is a novel sero-diagnostic marker for lung cancer. Issue 2 (November 2015) - Kobayashi, Makoto; Nagashio, Ryo; Jiang, Shi-Xu; Saito, Keita; Tsuchiya, Benio; Ryuge, Shinichiro; Katono, Ken; Nakashima, Hiroyasu; Fukuda, Eriko; Goshima, Naoki; Satoh, Yukitoshi; Masuda, Noriyuki; et al.
Highlights: Monoclonal antibody for CANX protein was established by the random immunization method. Serum levels of CANX protein in lung cancer patients were detected by the RPPA method. CANX protein is a useful early sero-diagnostic marker for lung cancer. Abstract: To develop sero-diagnostic markers for lung cancer, we generated monoclonal antibodies using lung adenocarcinoma (AC)-derived A549 cells as antigens by employing the random immunization method. Hybridoma supernatants were immunohistochemically screened for antibodies with AMeX-fixed and paraffin-embedded A549 cell preparations. Positive clones were monocloned twice through limiting dilutions. From the obtained monoclonal antibodies, one designated as KU-Lad-001 was recognized as calnexin (CANX) based on immunoprecipitation and MADLI TOF/TOF-MS analysis. To evaluate the utility of this antibody as a sero-diagnostic marker for lung cancer, we performed reverse-phase protein array analysis with samples of 195 lung cancer patients and 100 healthy controls. The CANX expression levels were significantly higher in lung cancer patients than in healthy controls ( P  < 0.0001), and the area under the curve of ROC was 0.980, with 96.9% specificity and 99.0% sensitivity. Furthermore, since CANX was also detected in stage I disease, the serum CANX levels should be applicable markers discriminating lung cancer patients from healthy controls and possibly used in the detection of early lung cancer. To our knowledge, the present results provide evidence that CANX may be a novel sero-diagnostic marker for lung cancer.